Britain after the Romans : an interdisciplinary approach to the possibilities of an Adventus Saxonum - Lloyd-Jones, Glyn Francis Michael (Rhodes University, Faculty of Humanities, School of Languages, 2015)
In the fifth century, after the departure of the Romans, according to tradition, which is based on the ancient written sources, Britain was invaded by the Angles and Saxons. This view has been questioned in the last century. The size of the 'invasion', and indeed its very existence, have come into doubt. However, this doubting school of thought does not seem to take into account all of the evidence. An interdisciplinary, nuanced approach has been taken in this thesis. Firstly, the question of Germanic raiding has been examined, with reference to the Saxon Shore defences. It is argued that these defences, in their geographical context, point to the likelihood of raiding. Then the written sources have been re-examined, as well as physical artefacts. In addition to geography, literature and archaeology (the disciplines which are most commonly used when the coming of the Angles and Saxons is investigated), linguistic and genetic data have been examined. The fields of linguistics and genetics, which have not often both been taken into consideration with previous approaches, add a number of valuable insights. This nuanced approach yields a picture of events that rules out the 'traditional view' in some ways, such as the idea that the Saxons exterminated the Britons altogether, but corroborates it in other ways. There was an invasion of a kind (of Angles "“ not Saxons), who came in comparatively small numbers, but found in Britain a society already mixed and comprising Celtic and Germanic-speaking peoples: a society implied by Caesar and Tacitus and corroborated by linguistic and genetic data.
Keywords: Great Britain -- History -- Anglo-Saxon period, 449-1066; Civilization, Anglo-Saxon; English philology -- Old English, ca. 450-1100; English literature -- Old English, ca. 450-1100; Anglo-Saxon race; Genetic genealogy